Penetapan Klaster Siswa Unggul Dengan Menggunakan Algoritma Roc-Smarter - Armiady, Dedy; Muslem R., Imam (Jurnal Tika, 2022)
The development of the IT world today has penetrated into all sectors of human life, one of which is the education sector. However, the implementation that occurs in the field has not been fully maximized, considering that there are still educational institutions that still seem half-hearted in implementing information technology. This happens due to various problems, such as lack of funds for IT development, IT infrastructure that is still minimal, especially for educational institutions located far from urban areas, human resources that are still lacking in skills and knowledge and various factors. Many efforts can be taken to improve this, one of which is as carried out in this study. The focus of this research is to develop an application by applying the ROC-SMARTER method so that it can be used by MTsN 2 Bireuen in determining the superior student cluster. From the implementation of the research using the ADDIE approach (Analyze, Design, Development, Implementation, and Evaluation) it was found that the case of determining the cluster of superior students at MTsN 2 Bireuen could be solved effectively and efficiently where previously it was done using manual and traditional methods